HUBUNGAN KOMPETENSI DAN LINGKUNGAN KERJA DENGAN KINERJA PEGAWAI DINAS PEMUDA DAN OLAH RAGA DI KOTA GORONTALO - Abdul Rahmat (Jurnal Manajemen., 2015)
The purpose of this study to describe the relationship of competence and work environment with employee performance Department of Youth and Sports in the city of Gorontalo. This is a survey research design, to test the hypothesis of the study and interpretation of the relationship of independent variables with the dependent variable. Population and sample in this study was overall employee in the Department of Youth and Sports Gorontalo 47 people. The main instrument was a questionnaire. The results showed: the relationship competence with employee performance belong to the category of very significant; relationship work environment with employee performance level categorized workplace relationships with significant categorized employee performance; relationship competence (X1) and work environment (X2) together with employee performance (Y) level relations Competence and Working Environment together with the very significant categorized Employee Performance.